2009
DOI: 10.1074/jbc.m109.040063
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ionizable Groups in Catalysis of Human Liver Glycolate Oxidase

Abstract: Glycolate oxidase is a flavin-dependent, peroxisomal enzyme that oxidizes ␣-hydroxy acids to the corresponding ␣-keto acids, with reduction of oxygen to H 2 O 2 . In plants, the enzyme participates in photorespiration. In humans, it is a potential drug target for treatment of primary hyperoxaluria, a genetic disorder where overproduction of oxalate results in the formation of kidney stones. In this study, steady-state and presteady-state kinetic approaches have been used to determine how pH affects the kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…In this work, recombinant His-tagged GOX enzymes from A. thaliana (C 3 species) and Z. mays (C 4 species) were compared ( Table 1). The obtained kinetic parameters agreed with previous K m(glycolate) values from plant-purified GOXs (0.3 mM in pumpkin cotyledons (13) and P. sativum leaves (14)) and recombinant mammalian GOX (0.32 mM in human (20) for purified and recombinant human liver GOXs (11,21). Therefore, our GOX proteins appear to be fully functional.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this work, recombinant His-tagged GOX enzymes from A. thaliana (C 3 species) and Z. mays (C 4 species) were compared ( Table 1). The obtained kinetic parameters agreed with previous K m(glycolate) values from plant-purified GOXs (0.3 mM in pumpkin cotyledons (13) and P. sativum leaves (14)) and recombinant mammalian GOX (0.32 mM in human (20) for purified and recombinant human liver GOXs (11,21). Therefore, our GOX proteins appear to be fully functional.…”
Section: Discussionsupporting
confidence: 76%
“…We nevertheless recognize that other effects may have contributed to the observed SIE such as an effect of solvent viscosity, which is indeed higher in heavy water (36). In fact, recombinant human liver GOX has lower k cat and k cat /K m values in a more viscous solvent such as glycerol (21). Also, three water molecules have been reported to participate in the catalytic site architecture in recombinant spinach GOX, and their presumed role is to maintain the H-bond network around FMN in the absence of glycolate (6,37 (38).…”
Section: Atgox1mentioning
confidence: 98%
“…Recombinant pure HsGOX was obtained as published. 16 [2R-2 H]Glycolate and glycolate were synthesized in our laboratory as described in the Supporting Information (SI). All other chemicals were of the highest purity commercially available.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These results suggested that glycerol might act as a competitive inhibitor in the HsGOX reaction. This hypothesis was ruled out on the basis of the fact that the HsGOX K m value with glycolate (0.05 mM at pH 7.0, 30 °C, and atmospheric oxygen) does not change in the presence of 6, 14, 21, and 28% (m/m) glycerol (unpublished data obtained for ref 16). Alternatively, the interactions in the HsGOX-glycolate complex may be weaker due to the presence of glycerol since this compound can affect various solvent and enzyme properties besides viscosity.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the first half-reaction, glycolate is oxidized to glyoxylate and the flavin is reduced. In the second half reaction, the cofactor FMN is reoxidized by the action of O 2 , resulting in the formation of H 2 O 2 [ 85 , 96 ].…”
Section: Enzyme Inhibitors For the Treatment Of Phsmentioning
confidence: 99%